Hepatitis B surface antigen genetic elements critical for immune escape correlate with hepatitis B virus reactivation upon immunosuppression. Issue 3 (28th January 2015) - Salpini, Romina; Colagrossi, Luna; Bellocchi, Maria Concetta; Surdo, Matteo; Becker, Christina; Alteri, Claudia; Aragri, Marianna; Ricciardi, Alessandra; Armenia, Daniele; Pollicita, Michela; Di Santo, Fabiola; Carioti, Luca; et al.
<x xml:space="preserve">Abstract</x> Hepatitis B virus (HBV) reactivation during immunosuppression can lead to severe acute hepatitis, fulminant liver failure, and death. Here, we investigated hepatitis B surface antigen (HBsAg) genetic features underlying this phenomenon by analyzing 93 patients: 29 developing HBV reactivation and 64 consecutive patients with chronic HBV infection (as control). HBsAg genetic diversity was analyzed by population‐based and ultradeep sequencing (UDS). Before HBV reactivation, 51.7% of patients were isolated hepatitis B core antibody (anti‐HBc) positive, 31.0% inactive carriers, 6.9% anti‐HBc/anti‐HBs (hepatitis B surface antibody) positive, 6.9% isolated anti‐HBs positive, and 3.4% had an overt HBV infection. Of HBV‐reactivated patients, 51.7% were treated with rituximab, 34.5% with different chemotherapeutics, and 13.8% with corticosteroids only for inflammatory diseases. In total, 75.9% of HBV‐reactivated patients (vs. 3.1% of control patients; P < 0.001) carried HBsAg mutations localized in immune‐active HBsAg regions. Of the 13 HBsAg mutations found in these patients, 8 of 13 (M103I‐L109I‐T118K‐P120A‐Y134H‐S143L‐D144E‐S171F) reside in a major hydrophilic loop (target of neutralizing antibodies [Abs]); some of them are already known to hamper HBsAg recognition by humoral response. The remaining five (C48G‐V96A‐L175S‐G185E‐V190A) are localized in class I/II–restricted T‐cell epitopes, suggesting a role in HBV escape from T‐cell‐mediated responses. By UDS, these mutations occurred in HBV‐reactivated patients with a median intrapatient prevalence of 73.3% (range, 27.6%‐100%) supporting their fixation in the viral population as a predominant species. In control patients carrying such mutations, their median intrapatient prevalence was 4.6% (range, 2.5%‐11.3%; P < 0.001). Finally, additional N‐linked glycosylation (NLG) sites within the major hydrophilic loop were found in 24.1% of HBV‐reactivated patients (vs. 0% of chronic patients; P < 0.001); 5 of 7 patients carrying these sites remained HBsAg negative despite HBV reactivation. NLG can mask immunogenic epitopes, abrogating HBsAg recognition by Abs. Conclusion: HBV reactivation occurs in a wide variety of clinical settings requiring immune‐suppressive therapy, and correlates with HBsAg mutations endowed with enhanced capability to evade immune response. This highlights the need for careful patient monitoring in all immunosuppressive settings at reactivation risk and of establishing a prompt therapy to prevent HBV‐related clinical complications. (Hepatology 2015;61:823–833)